2014
DOI: 10.1177/1756287214556643
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized comparative study of monopolar transurethral resection of the prostate versus photoselective vaporization of the prostate with GreenLight 120-W laser, in prostates less than 80 cc

Abstract: Objective: In this study we aimed to compare photoselective vaporization (PVP) with the GreenLight 120-W Laser and monopolar transurethral resection as surgical treatments of prostates less than 80 cc in men with obstructive benign prostatic hyperplasia. Methods: From February 2009 to March 2012 we allocated 101 patients with a prostate glands of less than 80 cc; patients were randomly assigned for surgical treatment with monopolar transurethral resection of the prostate (TURP) (n = 62) or PVP (n = 39). Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…1286 studies were identified through electronic searches and nine studies through additional searching. Thirty-six studies with 40 published articles (3831 participants) were finally included in our study 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1286 studies were identified through electronic searches and nine studies through additional searching. Thirty-six studies with 40 published articles (3831 participants) were finally included in our study 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Re-operation was analyzed as other complications-related outcomes and was reported in 13 studies 5 9 11 16 18 21 22 28 32 33 34 35 36 38 41 . However, the reasons for re-operation were not adequately interpreted in all included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As PVP has emerged as an alternative to MTURP in the treatment of BPH, several valuable randomized controlled trials (RCTs) have compared the surgical efficacy and safety of MTURP and PVP [ 7 8 9 10 11 12 13 14 15 16 17 ]. Thus, we performed a systematic review and meta-analysis of these RCTs in order to compare MTURP and PVP and to be able to provide the most up-to-date and reliable recommendations possible.…”
Section: Introductionmentioning
confidence: 99%
“…The authors claim that postoperative functional improvements were durable and equivalent in the two groups. Both techniques had a similar complication rate, however, hospital stay after laser procedure was significantly shorter [ 24 ]. Early outcomes of new 180-W XPS GreenLight laser system have been recently reported.…”
Section: Introductionmentioning
confidence: 99%